The Influence Of Product Quality, Packaging, And Brand Image On Gift-Giving Behavior Through Sentimental Value In Pretty Missy Brand Toys - Arsih, Yayuk Budhi; Harwani, Yuli (Al-Makki Publisher, 2024)
This research was conducted because of the importance of understanding the factors that influence gift-giving behavior in toys, especially in a competitive market. This study aims to determine and analyze the effect of product quality, packaging, and brand image on gift-giving behavior through the sentimental value of Pretty Missy brand toys. This research is included in the type of quantitative research. The population in the study were customers who made transactions at TK Retail and domiciled in the Greater Jakarta area, known in the period May - October 2023 totaling 844,022 customers, with a total minimum sample required of 204 samples where the sampling technique used was purposive sampling technique. The data analysis method uses the Structural Equation Model-Partial Least Square (SEM-PLS). The results of this study indicate that product quality, packaging, and brand image, have a positive effect on sentimental value in Pretty Missy brand toys. Sentimental value and product quality have a positive effect on gift-giving behavior on Pretty Missy brand toys. Packaging has a positive but insignificant effect on gift-giving behavior on Pretty Missy brand toys. Brand image has a positive but insignificant effect on gift-giving behavior on Pretty Missy brand toys. Product quality has a positive and significant effect on gift-giving behavior through sentimental value. Packaging has a positive and significant effect on gift-giving behavior through sentimental value. Brand image has a positive and significant effect on gift-giving behavior through sentimental value. The advice that can be given is that Pretty Missy should focus on increasing the comfort level of its products and conduct product testing with children and parents to provide better input. The advice that can be given is that Pretty Missy should focus on increasing the comfort level of its products and conduct product testing with children and parents to provide better input.